Stock market reaction to global supply chain disruptions from the 2018 US government ban on ZTE - Jacobs, Brian W.; Singhal, Vinod R.; Zhan, Xinrui (Journal of Operations Management, 2022)
AbstractGovernment trade actions are an increasing source of supply chain risk. This research provides empirical evidence of the stock market reaction to trade actions against a targeted firm on other firms in the targeted firm's supply chain eco‐system. We test our hypothesized stock price effects using the case of the 2018 US government ban on US firms from supplying to ZTE, a Chinese telecommunications manufacturer. We estimate the ban's effects on ZTE's tier‐one US and non‐US suppliers, as well as the upstream and downstream supply chain propagation effects by considering ZTE's tier‐two suppliers and business customers. We also estimate impacts to ZTE's competitors. We find that tier‐one US suppliers experienced a stock price effect of −3.33% following the ban, and the reaction was more negative for those suppliers more dependent on ZTE for revenues. We find a stock price effect on tier‐two suppliers of −0.40%, but an insignificant effect on non‐US tier‐one suppliers. Business customers experienced a stock price effect of 0.66%, and the competitors' stock price effect was 1.34%. The reversal of the ban 4 weeks later resulted in a stock price effect of 1.56% for tier‐one US suppliers, 1.72% for tier‐one non‐US suppliers, and 1.35% for competitors.